2022
DOI: 10.12669/pjms.38.7.6144
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of resistance to first-line antiretroviral therapy observed among HIV patients

Abstract: Objectives: This study aimed to assess the frequency of first-line antiretroviral therapy (ART) resistance among HIV patients and to identify the factors affecting the drug resistance. Methods: A cross-sectional study was conducted over a sample of 162 HIV-positive patients attending the Medicine Department of Lady Reading Hospital, Peshawar-Pakistan, from July 2020 to January 2021. Blood samples were collected for phylogenic profiles to determine first-line antiretroviral therapy resistance. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several studies have shown an alarming increase in drug resistance to antiretroviral drugs, including acquired resistance, which complicates the effective treatment of the disease [1][2][3][4]. Indeed, the likelihood of developing resistance to at least one antiretroviral drug is high and can lead to treatment failure in about 65% of cases [5]. In particular, the development of resistance to both nucleoside and non-nucleoside reverse transcriptase inhibitors, the main classes of drugs used to treat HIV, now exceeds 50% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an alarming increase in drug resistance to antiretroviral drugs, including acquired resistance, which complicates the effective treatment of the disease [1][2][3][4]. Indeed, the likelihood of developing resistance to at least one antiretroviral drug is high and can lead to treatment failure in about 65% of cases [5]. In particular, the development of resistance to both nucleoside and non-nucleoside reverse transcriptase inhibitors, the main classes of drugs used to treat HIV, now exceeds 50% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most cases are asymptomatic and can affect people of any gender and age, but it is more common among men, and symptoms usually appear in adults and adolescents. 1 The major symptoms of septal deviation are nasal obstruction causing difficulty in breathing. 2 Other common symptoms include nasal blockage, bleeding, headache, hypoxemia, sinusitis, hypoxemia, cosmetic deformity, and septoplasty.…”
Section: Introductionmentioning
confidence: 99%